Humane Humanitarians : A Study of Personal Characteristics of Emergency Relief Workers - Meduri, Yamini; Ahmed, Fakruddin Ali (Prabandhan: Indian Journal of Management, 2017)
Emergency relief workers have played a crucial role in every disaster management operation that has occurred so far, and the future is no different. The current study attempted to understand the different competencies of a humanitarian logistician as required by the relief organizations so that a comprehensive competency model can be build which shall support the personnel decisions in the future. To achieve this, a brief review of literature followed by content analysis of job advertisements was undertaken by 23 independent coders to understand the competencies required. The current study considered the underlying personal characteristics that contribute to the expected behaviors on the field. Fourteen personal competencies were derived, which were ranked based on the frequency weightages and a comprehensive competency model with behavioral indicators is presented in this study. The research also revealed that the personality traits of an individual also determine the effectiveness of his/her contribution in a relief operation.